Pendayagunaan Zakat Poduktif dalam Meningkatan Usaha Mustahik (Studi Kasus pada Badan Amil Zakat Nasional Kabupaten Bengkulu Selatan) - Intan Nirmala Dewi; Hak, Nurul; Sumarni, Yenti (Faculty of Islamic Economics and Business, Madura Islamic State University, 2023)
ABSTRACT This research aims to find out the productive zakat utilization model carried out by BAZNAS South Bengkulu Regency and to find out the improvement of mustahik businesses after receiving productive zakat assistance from BAZNAS South Bengkulu Regency. This research method is structured using a type of field research with a descriptive qualitative approach. Techniques used in data collection are observation, interviews and documentation. The data analysis technique used was carried out through the steps of data reduction, data presentation and drawing conclusions. The results of this activity show that the utilization of productive zakat at BAZNAS South Bengkulu Regency in improving mustahik businesses is realized in productive economic programs, as well as with management in the form of creative productive zakat. The increase in mustahik businesses in productive zakat from BAZNAS South Bengkulu Regency is increasing well. This can be seen from the mustahik income data table after receiving effective assistance from zakat. Keywords: Productive Zakat Utilization, Business Improvement